Optimization of Search Engine contents (International Journal of Engineering and Computer Science, 2015)
As an information resource the Internet is increasing in size, depth and complexity. Availability of information is no longer an issue on the Internet. In an era where human presence is worth so much, it is becoming increasingly time consuming to analyze the relevant information from an ever-growing sea of inadequate or inappropriate data and accelerate the laborious process of web browsing. Information provided by search engines to web users is irrelevant, due to the lack of providing structural information and categorization of the documents. The issue of uncategorized data has become a standoff due to the inconsistencies and variations in the characteristics of the data. In this paper, we present a way to cut short the sea of data to relevant data by forming categories and then providing summarized data with links in specific category. The projected way has insightful ability to improve the drawback and returns efficient outcomes.